Utilization of CO2 as a partial substitute for methane feedstock in chemical looping methane–steam redox processes for syngas production. Issue 6 (21st February 2017) - Kathe, Mandar; Empfield, Abbey; Sandvik, Peter; Fryer, Charles; Zhang, Yitao; Blair, Elena; Fan, Liang-Shih
Abstract : This work describes the capability of a novel chemical looping system that utilizes CO2 as a feedstock for methane reforming. Abstract : This work describes the unique capability of a novel chemical looping system that utilizes CO2 as a feedstock for methane reforming. This system uses an iron–titanium composite metal oxide and a co-current moving bed reactor system to yield a higher purity of syngas than the conventional CO2 dry reforming system.